An analysis of unemployment determinants in South Africa, Greece, and Spain / Nurul Syafinaz Amalina Zulbaha - Zulbaha, Nurul Syafinaz Amalina (2017)
Unemployment is a major macroeconomic problem that facing by the most developing countries. It is a situation in which people willing and capable of working are unable to find suitable jobs to earn a living. The main purpose of this research is to examine the determinant of unemployment rate in South Africa, Greece, and Spain. The three determinants are Gross Domestic Product, Population, and Foreign Direct Investr-nent. Three countries from Organisation for Economic Co-operation and Development (OECD) have been choosing as a sample. The research objective is to examine the relationship between unemployment rate with Gross Domestic Product, Population, and Foreign Direct Investment. This research wills using quantitative data in the form of exploratory statistic to analyse the determinant of unemployment. The duration of the study is from 1999 to 2016 with fifty-four observations. Panel data will be employed as the research method. Data will be collected from World Bank and OECD. In the expected findings, all independent has significant relationship with unemployment rate. Population has positive relationship with unemployment rate. Gross Domestic Product and Foreign Direct Investment have negative relationship with unemployment rate.